STRATEGI PENGEMBANGAN TEKNIK PEMBUATAN PRODUKPRODUK KULIT UNTUK MENINGKATKAN KEMAMPUAN KREATIF DI INDUSTRI KECIL/MENENGAH ALAS KAKI CIBADUYUT - Mohamad Arif Waskito (Jurnal Dimensi Seni Rupa dan Desain, 2014)
The creative process in industrial product development in small / medium often don't have opportunity to explore the design, especially in industries which only prioritize production activities only. Their activities will be dominated by the action that refers to the effectiveness and efficiency of production. The production process will be determined based on the speed and reduced their production cost. As happens in many footwear industry in Cibaduyut, generally they will act as the industry "partners" who would accept a job just to make the shoes of larger industry known as "The Champion". Due to the design and technical specifications of products produced by small-scale industries have been set by the industry "Champion", then the selling value the product that can be offered only on quality of workmanship and low cost of production (hpp). Build creative abilities in a small industry is becoming increasingly difficult because of their perceptions of the development of new products based on originality will require many experiments with the high cost and uncertainty of the results. In addition, if the new product has been produced, it will require new skills and new equipment to be purchased. It also makes SMEs often avoid the effort to develop creative products. In this study, will be made efforts to develop creative products that can be done by small industry through product diversification strategy, based on the principle of common production techniques in the industry without requiring a large investment. The process of formation will use mould and knit technique as applyed in the footwear industry, but will be used for other products besides footwear products. Abstrak Proses kreatif dalam pengembangan produk industri kecil / menengah sering tidak memiliki kesempatan untuk menjelajahi Desain, terutama dalam industri yang hanya memprioritaskan kegiatan produksi. Kegiatan mereka akan didominasi oleh tindakan yang mengacu pada efektifitas dan efisiensi produksi. Proses produksi akan ditentukan berdasarkan kecepatan dan mengurangi biaya produksi mereka. Seperti yang terjadi di banyak industri alas kaki di Cibaduyut, umumnya mereka akan bertindak sebagai industri "mitra" yang akan menerima pekerjaan hanya untuk membuat sepatu industri besar yang dikenal sebagai "The Champion". Karena desain dan teknis spesifikasi produk yang diproduksi oleh industri skala kecil telah ditetapkan oleh industri "Champion", maka nilai jual produk yang dapat ditawarkan hanya pada kualitas pengerjaan dan rendah biaya produksi (hpp). Membangun kemampuan kreatif dalam industri kecil menjadi semakin sulit karena persepsi mereka tentang pengembangan produk baru berdasarkan orisinalitas akan memerlukan banyak percobaan dengan tingginya biaya dan ketidakpastian hasil. Selain itu, jika produk baru telah diproduksi, itu akan membutuhkan keterampilan baru dan peralatan baru untuk dibeli. Hal ini juga membuat UKM sering menghindari upaya untuk mengembangkan produk-produk kreatif. Dalam studi ini, akan dilakukan upaya untuk mengembangkan produkproduk kreatif yang dapat dilakukan oleh industri kecil melalui strategi diversifikasi produk, berdasarkan prinsip umum teknik produksi dalam industri tanpa memerlukan investasi besar. Proses pembentukan akan menggunakan cetakan dan teknik rajut sebagai diterapkan di industri alas kaki, tetap